Zwei neue Sphaerodoridae (Polychaeta/Meiofauna) aus der Adria. - Katzmann, Werner (Annalen des Naturhistorischen Museums in Wien, 1973)
Two new species of Sphaerodoridae are described from the Adriatic Sea. Sphaerodoridium longiparapodium n. sp. is especially characterized by the absence of eyes, the length of parapodia, four dorsal rows of spheric big sessile macrotubercles, and also by the extremly long distal parts of the composite setae. Clavodorum adriaticum n. sp. is characterized by six dorsal rows of stalked macrotubercles, and by one pair of big subdermal eyes. The ventrum is covered by numerous small stalked tubercles. Both species were found in mixed sediments of mud and sand in the central part of the Adriatic Sea from depths from 20 to 60 metres.
AnnelidaBase